Pertanggungjawaban Hukum Korporasi: Penegakan Hukum terhadap Pencemaran dan Kerusakan Lingkungan Hidup di Indonesia - Dila Nurul Maghfira Arrahman; Gia Anggiani; Allisya Destari Pratami; Hani Sri Handayani (Journal of Legal, Political, and Humanistic Inquiry, 2025)
Corporate legal liability plays a crucial role in addressing environmental pollution and degradation in Indonesia, particularly in the context of increasing industrial and corporate activities. This study examines the enforcement of law against corporations responsible for environmental damage, focusing on the normative framework, practical challenges, and effectiveness of existing legal mechanisms. Using a normative juridical method, the research analyzes statutory regulations, legal doctrines, and relevant court decisions related to corporate criminal liability in environmental cases. The findings indicate that although Indonesian environmental law provides comprehensive instruments, including criminal, civil, and administrative sanctions, law enforcement remains suboptimal due to evidentiary difficulties, complex corporate structures, institutional limitations, and weak inter-agency coordination. These obstacles often reduce the deterrent effect of sanctions and hinder environmental restoration efforts. The study emphasizes the importance of strengthening institutional capacity, adopting a progressive judicial approach, and ensuring consistent enforcement to enhance corporate accountability. Effective enforcement of corporate liability is essential to safeguard environmental sustainability, protect public interests, and ensure justice for present and future generations